2001
DOI: 10.1073/pnas.071615398
|View full text |Cite
|
Sign up to set email alerts
|

Tissue spreading on implantable substrates is a competitive outcome of cell–cell vs. cell–substratum adhesivity

Abstract: While the interactions of cells with polymeric substrata are widely studied, the influence of cell-cell cohesivity on tissue spreading has not been rigorously investigated. Here we demonstrate that the rate of tissue spreading over a two-dimensional substratum reflects a competition or ''tug-of-war'' between cell-cell and cellsubstratum adhesions. We have generated both a ''library'' of structurally related copolymeric substrata varying in their adhesivity to cells and a library of genetically engineered cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
217
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 37 publications
8
217
1
2
Order By: Relevance
“…We used gels with differing chemical composition. The relative importance of cell-cell and cell-matrix interactions has been investigated quantitatively (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used gels with differing chemical composition. The relative importance of cell-cell and cell-matrix interactions has been investigated quantitatively (11).…”
Section: Resultsmentioning
confidence: 99%
“…Cell aggregates have traditionally been used as a powerful tool to understand the principles of cell-cell (10) and cell-matrix adhesion (11), as well as cell sorting (12). In addition, rapid prototyping technology has successfully been applied for computer-aided deposition of cells in gels to create 3D tissue constructs (13,14).…”
mentioning
confidence: 99%
“…Recently, important insights have been gained regarding the possible mechanism of aggregate fusion in the presence of extracellular matrix (Ryan et al, 2001). It was demonstrated that competition exists between cell-to-cell forces vs. cell-to-substrate forces.…”
Section: Role Of Gel and Close Positioning In Promoting The Fusion Ofmentioning
confidence: 99%
“…Although studies have reported that cell-cell cohesivity through cadherins competitively decreases cell-substratum adhesivity, a process known as contact inhibition of cell adhesion and spreading (Yap and Manley, 1993;Ryan et al, 2001), an explanation for the underlying mechanism remains elusive. Cadherin engagement between cells leads to the formation of adherens junctions, the cytoplasmic face of which consists of an adhesion plaque containing many of the same structural proteins as are found in FAs (Pokutta and Weis, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, changes in the engagement of vascular endothelial (VE)-cadherin, the principal junctional molecule in endothelial cells (Dejana et al, 1999), alter both biochemical pathways, such as vascular endothelial growth factor (VEGF) and cell survival signaling (Carmeliet et al, 1999), as well as mechanical states by altering cytoskeletal organization and the local transfer of mechanical stress (Shay-Salit et al, 2002). Although the biochemical and mechanical consequences of integrin-and cadherin-mediated adhesion each have been described, how these adhesions cross talk and cooperate is less well understood.Although studies have reported that cell-cell cohesivity through cadherins competitively decreases cell-substratum adhesivity, a process known as contact inhibition of cell adhesion and spreading (Yap and Manley, 1993;Ryan et al, 2001), an explanation for the underlying mechanism remains elusive. Cadherin engagement between cells leads to the formation of adherens junctions, the cytoplasmic face of which consists of an adhesion plaque containing many of the same structural proteins as are found in FAs (Pokutta and Weis, 2002).…”
mentioning
confidence: 99%